The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.apenergy.2016.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of system improvements in solar thermal and air source heat pump combisystems

Abstract: International audienceA solar thermal and heat pump combisystem is one of many system alternatives on the market for supplying domestic hot water (DHW) and space heating (SH) in dwellings. In this study a reference solar thermal and air source heat pump combisystem was defined and modelled based on products available on the market. Based on the results of an extensive literature survey, several system variations were investigated to show the influence of heat pump cycle, thermal storage and system integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Using a logarithmic equation to regress the relationship of COP h with temperature difference between supply water and outdoor air, it could be written as Equation (9) COP h = −2.437 ln(t s,w − t o,a ) + 12.418 (9) From the study of Chen et al [6], the COP of heat pump should be above 3 to achieve lower cost and less environment impact than other heating systems. To get the reasonable COP h , the temperature difference between outdoor air and supply water of ASHP using RHR-1 is suggested to be controlled within 47.5 • C. Considering the temperature difference between supply water and indoor air, this result accords with the study by Zhang et al [8] that indicated that the application of ASHP should control indoor and outdoor air temperature be within 41 • C to achieve an acceptable COP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a logarithmic equation to regress the relationship of COP h with temperature difference between supply water and outdoor air, it could be written as Equation (9) COP h = −2.437 ln(t s,w − t o,a ) + 12.418 (9) From the study of Chen et al [6], the COP of heat pump should be above 3 to achieve lower cost and less environment impact than other heating systems. To get the reasonable COP h , the temperature difference between outdoor air and supply water of ASHP using RHR-1 is suggested to be controlled within 47.5 • C. Considering the temperature difference between supply water and indoor air, this result accords with the study by Zhang et al [8] that indicated that the application of ASHP should control indoor and outdoor air temperature be within 41 • C to achieve an acceptable COP.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [8] reported the application of ASHP for heating in Harbin which showed the temperature difference between indoor and outdoor air should be controlled within 41 • C to achieve an acceptable COP. Poppi et al [9] evaluated solar thermal and ASHP combisystems which indicated that variations in electricity price affect the additional investment far more than other economic parameters and the potential for achieving cost benefit vary a lot depending on load and climate boundary conditions. Braun and Rowley [10] indicated that heat pumps can realize emissions reductions when installed at high penetration levels combined with a grid decarbonization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Kaygusuz et al introduced energy storage tank in a dual source combined heat pump system to reduce the energy unbalance between the supply side and demand side of the system, and the energy storage played a vital role in energy conservation and could enhance the efficiency and reliability of the system [18]. Poppi et al modeled an air source and solar thermal heat pump combisystem to investigate the impact of component size on electricity demand and optimized the system performance by employing variable speed compressor, four-way valve and vacuum insulation technique [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…After that, the boundary conditions of the system could also directly affect the system energy consumption. 11,12 Cai et al used numerical simulation and experimental tests to find that during the heating process of solar assisted systems, the COP increased with the increase of solar radiation. When the solar radiation was 0 W/m 2 , the heat pump COP was 2.35, and when the solar radiation was 800 W/m 2 , the heat pump COP was 2.57.…”
Section: Introductionmentioning
confidence: 99%